2004
DOI: 10.1002/chin.200424215
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Piperidines

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…It has been previously reported that the melting temperature of gold nanoparticles is size-dependent. 11 For a gold nanoparticle of 6 nm diameter, the reported melting temperature is about 1000 °C. 12,13 It is also observed that the nanoparticles disappear immediately after melting.…”
Section: T H Imentioning
confidence: 99%
“…It has been previously reported that the melting temperature of gold nanoparticles is size-dependent. 11 For a gold nanoparticle of 6 nm diameter, the reported melting temperature is about 1000 °C. 12,13 It is also observed that the nanoparticles disappear immediately after melting.…”
Section: T H Imentioning
confidence: 99%